Cognates Recognition: Its Effect on the Reading Comprehension of Scientific Texts - BOUTEBDJA, Lamia (Journal of Human Sciences, 2024)
For decades, researchers have indicated the relevant role that cognates play in reading comprehension due to the lot of benefits these words can produce. In this respect, our article aims at discussing one of the reading strategies used by students of Biology at Constantine University 1 in understanding scientific terminology which is recognising the English cognates for the French scientific terms. Also, it investigates the extent to which the use of such strategy enhances the reading comprehension of English biology texts. The hypothesis is that: if students use the strategy of recognising cognates for understanding scientific terminology, their comprehension of biology texts will be better and faster.